Motivasi Belajar dan Adaptasi Siswa Pondok Pesantren - Eriyono Budi Wijoyo; Dela Novitasari; Roswita Hasan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Adolescence is a transition from child to adult, which requires strong effort because this is a period of adaptation. So research is needed which aims to determine the learning motivation of Islamic boarding school youth in relation to their adaptation. This study applied a cross-sectional design, involving 55 students who were taken by purposive sampling. The independent variable in this study was learning motivation, while the dependent variable was adolescent adaptation. Both of these variables were measured by filling out adaptation and learning motivation questionnaires. The data that had been collected was analyzed using the Chi-square test in order to test the correlation of the two variables. The results of the analysis showed that the p-value was less than 0.05. Furthermore, it was concluded that there is a relationship between learning motivation and adaptation of Islamic boarding school students.Keywords: boarding school; motivation to learn; student adaptation ABSTRAK Remaja merupakan peralihan dari anak menuju dewasa, yang membutuhkan usaha kuat karena ini merupakan masa untuk beradaptasi. Maka diperlukan penelitian yang bertujuan untuk mengetahui motivasi belajar remaja pesantren dalam kaitannya adaptasi mereka. Penelitian ini menerapkan desain cross-sectional, yang melibatkan 55 siswa yang diambil dengan cara purposive sampling. Variabel independen dalam studi ini adalah motivasi belajar, sedangkan variabel dependen adalah adaptasi remaja. Kedua variabel ini diukur melalui pengisian kuesioner adaptasi dan motivasi belajar. Data yang telah terkumpul dianalisis menggunakan uji Chi-square dalam rangka menguji korelasi kedua variabel. Hasil analisis menunjukkan bahwa nilai p kurang dari 0,05. Selanjutnya disimpulkan bahwa ada hubungan antara motivasi belajar dan adaptasi siswa pondok pesantren.Kata kunci: pesantren; motivasi belajar; adaptasi siswa